Distribution and survival of Borrelia miyamotoi in human blood components. Issue 3 (21st December 2015) - Thorp, Aaron M.; Tonnetti, Laura
Abstract : BACKGROUND: Borrelia miyamotoi, the agent of relapsing fever, is a tick‐borne spirochete first isolated in Japan in 1994. Since then, the spirochete has been detected in ticks globally, generally in the same vectors as the Lyme disease agent. Human infection has been reported in Russia, Europe, Japan, and the United States, as influenza‐like febrile illness. In addition, two cases of meningoencephalitis caused by B. miyamotoi have also been reported in immunocompromised patients. Here we evaluate the ability of the spirochete to survive in human blood components stored under standard blood bank conditions. STUDY DESIGN AND METHODS: Freshly collected human whole blood was spiked with in vitro cultured B. miyamotoi or B. miyamotoi –infected mouse plasma and separated into red blood cells (RBCs), plasma, and platelets. Components were either injected into immunocompromised (SCID) or wild‐type immunocompetent mice or cultured in vitro, right after separation and after storage at the appropriate conditions. Infection was monitored by microscopic observation, blood smears, and polymerase chain reaction. RESULTS: In vivo, all the SCID mice challenged with the components before storage and the RBCs stored for up to 42 days developed the infection. Wild‐type mice also developed the infection when injected with prestorage samples from all components, while a lower number of mice were infected by RBCs stored for 42 days. In vitro, spirochetes grew in all samples but frozen plasma. CONCLUSIONS: This study demonstrated that B. miyamotoi can survive standard storage conditions of most human blood components, suggesting the possibility of transmission by blood transfusion.